Prioritization of ergonomic risk assessment methods with if-ahp and proposal of an integrated method - Köşker, Tuğçenur (My University, 2019)
ERGONOMİK RİSK DEĞERLENDİRME YÖNTEMLERİNİN IF-AHP İLE ÖNCELİKLENDİRİLMESİ VE BÜTÜNLEŞİK BİR MODEL ÖNERİSİİnsan ve ekipman, makine ve çalışma ortamı dahil tüm faktörler arasındaki etkileşimin kalitesine odaklanan ergonomi, akademik çalışmalarda ve pratik uygulamalarda uzun yıllar boyunca önemli bir konu olmuştur. Ergonomi ilkelerini uygulayarak rahat ve sürdürülebilir bir çalışma ortamı sağlamak amaçlanmaktadır. Ayrıca, iyi ergonomi uygulamaları daha yüksek kalite performansı, artan iş güvenliği, müşteri ve çalışan memnuniyeti ile sonuçlanmaktadır. Ancak, ergonomi ihmal edilirse, çeşitli problemler ortaya çıkabilir. Özellikle, İşe Bağlı Kas-İskelet Hastalıkları, genellikle birkaç saatten fazla süren uygun olmayan duruşlar ve vücut hareketleri nedeniyle çeşitli sektörlerde yaygın sağlık sorunları olarak görülmüştür. Bu noktada, ergonomik risk değerlendirme yöntemleri muhtemel riskleri belirlemede büyük rol oynamaktadır. Hem imalat hem de hizmet sektöründe ergonomik riskleri değerlendirmek için çeşitli yöntemler vardır. Bu çalışmanın amacı, mevcut ergonomik risk değerlendime yöntemlerine dayalı olarak konsolide bir risk değerlendirme metodolojisi geliştirmektir. Bu amaç için, öncelikle mevcut ergonomik risk değerlendime yöntemleri, belirlenen kriterlere göre sezgisel bulanık analitik hiyerarşi süreci ile değerlendirilir. Daha sonra, risk seviyesinin nihai değerlendirmesi için bir puanlama ölçeği sunulur.

PRIORITIZATION OF ERGONOMIC RISK ASSESSMENT METHODS WITH IF-AHP AND PROPOSAL OF AN INTEGRATED METHODErgonomics which focuses on the quality of the interactive relation between the human and all the factors including equipment, machines and working environment has been an important topic both in academic studies and practical applications for many years. By implementing the ergonomics principles, it is aimed to provide a comfortable and sustainable working environment. Moreover, suitable ergonomics applications result in higher quality performance, increased occupational safety and satisfaction of customers and employees. However, if the ergonomics are neglected, various problems can occur. Especially, Work-Related Musculoskeletal Disorders have been seen as widespread health problems in multiple sectors as a result of body movements and unsuitable postures that are usually kept over periods of many hours. At this point, the ergonomic risk assessment methods play a significant role to identify the probable risks. There are various methods for evaluating the ergonomics risks both in the manufacturing and service sectors.The goal of this study is to develop a consolidated risk assessment methodology based on the existing ergonomic risk assessment methods. For the aim, firstly, the existing ergonomic risk assessment methods are evaluated via intuitionistic fuzzy analytic hierarchy process with respect to the determined criteria. Afterwards, a scoring scale is presented for the final assessment of risk level.
Keywords: Endüstri mühendisliği; Ergonomik risk değerlendirme; Industrial engineering; intuitionistic fuzzy analytic hierarchy process; kas-iskelet sistemi hastalıkları; musculoskeletal disorders; sezgisel bulanık analitik hiyerarşi prosesi Ergonomics risk assessment